2002
DOI: 10.4049/jimmunol.168.3.1167
|View full text |Cite
|
Sign up to set email alerts
|

Functional Avidity of Tumor Antigen-Specific CTL Recognition Directly Correlates with the Stability of MHC/Peptide Multimer Binding to TCR

Abstract: Avidity of Ag recognition by tumor-specific T cells is one of the main parameters that determines the potency of a tumor rejection Ag. In this study we show that the relative efficiency of staining of tumor Ag-specific T lymphocytes with the corresponding fluorescent MHC class I/peptide multimeric complexes can considerably vary with staining conditions and does not necessarily correlate with avidity of Ag recognition. Instead, we found a clear correlation between avidity of Ag recognition and the stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 22 publications
(20 reference statements)
5
75
0
Order By: Relevance
“…Initial reports suggested that the intensity of staining by tetrameric soluble MHC/peptide complexes (tetramers) could be used as a parameter to identify high avidity T cells (15)(16)(17)(18), and more recently it has been shown that stability of tetramer binding to T cell clones could be used to assess the affinity of TCR recognition (19,20). Brightness of tetramer staining, however, can be influenced by several factors, including tetramer internalization (19,21,22), whereas tetramer decay experiments require tetramer half-life measurements that cannot be easily conducted to sort high avidity T cell populations.…”
mentioning
confidence: 99%
“…Initial reports suggested that the intensity of staining by tetrameric soluble MHC/peptide complexes (tetramers) could be used as a parameter to identify high avidity T cells (15)(16)(17)(18), and more recently it has been shown that stability of tetramer binding to T cell clones could be used to assess the affinity of TCR recognition (19,20). Brightness of tetramer staining, however, can be influenced by several factors, including tetramer internalization (19,21,22), whereas tetramer decay experiments require tetramer half-life measurements that cannot be easily conducted to sort high avidity T cell populations.…”
mentioning
confidence: 99%
“…Preincubation with anti-CD8 mAb for 30 min followed by removal of unbound mAb by washing and incubation with multimers gave similar results. (21). We also observed that for a given clone, multimers incorporating weak agonist ligands displayed decreased binding efficiency compared with multimers incorporating full agonist ligands and faster off-rates (22).…”
Section: Decreased Pmhc Multimer Binding To Cd8 Does Not Affect Pmhc/mentioning
confidence: 66%
“…As illustrated in Fig. 3A, multimers containing the A2 A245V single mutant showed a highly decreased binding avidity on the MAGE-A10-specific clone 6D1 (21). Reduction in the specific binding avidity of A245V vs wild-type multimers was also observed in the case of Melan-A-specific clone 17 as well as in the case of other MAGE-A10-and Melan-A-specific clones that recognize the peptide with lower avidity (data not shown).…”
Section: Mutations In the A2 ␣3 Cd8-binding Domain Impact On The Bindmentioning
confidence: 66%
“…3C). According to some previous studies, this could indicate higher avidity of CTLs (17), although this may not always be the case (18).…”
Section: Ctl Priming By Low Mhc Density Aapcs Requires Costimulation mentioning
confidence: 97%